Efektivitas Prototipe Jembatan Penyeberangan Orang Ramah Lingkungan - Hendrawan, Hendra (MEDIA KOMUNIKASI TEKNIK SIPIL, 2022)
Pedestrians are road users who are prone to accidents. Several studies related to the effectiveness of providing pedestrian bridges in Indonesia have shown a low level of utilization of pedestrian bridges. This study aims to determine the efficacy of providing an environmentally friendly pedestrian bridge prototype that was built by considering user needs from planning, design, and aesthetic criteria. Data were obtained through field surveys to get information on traffic conditions and bridge users and interviews to obtain information about crossing purposes and perceptions of needs. Statistical analysis of the average difference test was carried out to prevent bias in traffic conditions. Furthermore, descriptive statistical analysis was carried out to determine the effectiveness of providing pedestrian bridges obtained from comparing data processing results with the evaluation table. The results showed that the environmentally friendly Pedestrian Bridge prototype did not guarantee an increase in the number of users. Coercion through law enforcement and the installation of dividing lanes on the lanes can be seen as a solution. However, aesthetic and sustainable design is a necessity.